Pemikiran Al-Ghazali dan Thomas Aquinas: Keadilan Harga - Siswadi Sululing; Alimuddin; Amiruddin (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to provide an overview of price fairness according to the thoughts of Al – Ghazali and Thomas Aquinas. Descriptive research using the primary data source Ihya Ulumiddin book, secondary data sources: books and journals. The data analysis method used descriptive qualitative. The results of the discussion that Al-Ghazali's thoughts offer fair selling price determination by considering the abilities and needs of buyers and sellers. The selling price based on the value of justice will try to improve the dignity of human life by paying attention to the purchasing power of the people, entrepreneurs are only required to fulfill their needs. Thomas Aquinas thought that a fair price has benefits for society that are considered necessary for the reproduction of social order, and are only sufficient to cover the costs of production, including the maintenance of a worker and his family so that the wages given are appropriate.